'The Party with God': Michel Foucault, the Gay Left and the Work of Theory. Issue 2 (October 2016) - Maynard, Steven
Abstract : Revisiting Foucault's month-long stay in Toronto in June 1982, this article explores the reception and appropriation of the first volume of The History of Sexuality by activist-intellectuals associated with the Toronto-based publication, The Body Politic, and some of their fellow travelers. Reading Foucault's introductory volume through the intersecting frameworks of social constructionism, historical materialism, and socialist feminism, gay-left activists forged a distinctive relationship between sexual theory and political practice. If Foucault had a significant impact on activists in the city, Toronto also left its mark on Foucault. Based on the recently rediscovered and unedited transcript of a well-known interview with Foucault in Toronto, along with an interview with one of Foucault's interlocutors, the article concludes with Foucault's forays into Toronto's sexual and political scenes, particularly in relation to 'bodies and pleasures' and resistance to the sex police.